PURPOSE OF INSTALLING AND IMPLYING OF WARNING AS A KIND OF PUNISHMENT - Danilov, Vyacheslav (Administrative and Criminal Justice, 2019)
The paper investigates the role of the establishment and appointment of such forms of punishment as prevention. This type of responsibility is practiced if the degree of misconduct is very slight and does not cause any damage to public order. The warning is a documented censure of an individual, a legal entity and is issued in a written form.